1997
DOI: 10.1002/(sici)1520-6408(1997)21:1<31::aid-dvg4>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Integrin trafficking regulates adhesion to fibronectin during differentiation of mouse peri‐implantation blastocysts

Abstract: Trophoblast cells of the peri-implantation blastocyst differentiate from a polarized epithelium, the trophectoderm, into invasive cells having an apical surface occupied by integrins that mediate adhesion to the extracellular matrix. Blastocyst differentiation was assessed during serum-free culture using a fibronectin binding assay with intact mouse blastocysts. Fibronectin binding activity became elevated during a 24-h "window" after approximately 72 h of culture. Blastocyst differentiation was unaffected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…3). This assay mimics the natural mechanism of adhesion of trophoblasts on the blastocysts to the endometrium which is regulated by interaction between the integrins naturally expressed on endometrial cells and on the apical surface of competent blastocysts [59][60]. By assessing the extension and adhesion of the hatched blastocysts it is possible to evaluate their developmental potential.…”
Section: Resultsmentioning
confidence: 99%
“…3). This assay mimics the natural mechanism of adhesion of trophoblasts on the blastocysts to the endometrium which is regulated by interaction between the integrins naturally expressed on endometrial cells and on the apical surface of competent blastocysts [59][60]. By assessing the extension and adhesion of the hatched blastocysts it is possible to evaluate their developmental potential.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has demonstrated that Integrin-b3 is a target of let-7a in the human HeLa cell line and in mouse blastocysts (11). Integrins are a family of transmembrane adhesion receptors and are primarily responsible for regulating the interactions between the trophoblasts and the extracellular matrix molecules of the endometrium (31). They are heterodimers composed of non-covalently associated α and β subunits that engage with extracellular matrix proteins and couple to intracellular signalling and cytoskeletal complexes (32).…”
Section: Discussionmentioning
confidence: 99%
“…Integrins αvβ3, α5β1 and α6Bβ1 are present in the early and late mouse blastocyst, whereas the α2, α6A and α7 subunits appear in the late blastocyst, and α1 appears only in outgrowths (Sutherland et al, 1988(Sutherland et al, , 1993; see also Box 2). In mice, binding of fibronectin, vitronectin or OPN to the blastocyst stimulates the trafficking of integrins to the mouse trophectodermal surface and the assembly of focal contact-like structures, as indicated by the presence of the focal adhesion markers vinculin and talin (Chaen et al, 2012;Schultz and Armant, 1995;Schultz et al, 1997;Yelian et al, 1995). Integrin signalling modulates trophoblast adhesion through the activation of phospholipase Cγ to initiate phosphoinositide signalling and intracellular Ca 2+ mobilisation Wang et al, 2007).…”
Section: Integrin Expression and Activation In The Blastocystmentioning
confidence: 99%